Efeito do exerc??cio aqu??tico na regenera????o do m??sculo esquel??tico ap??s crioles??o - Pestana, Paulo Roberto Dantas (2010)
Skeletal muscles are dynamic tissues that can alter their phenotypic characteristics, providing a better functional adaptation faced with various stimuli. OBJECTIVE: To investigate the influence of aquatic exercise on the expression of myogenic markers, during regeneration of skeletal muscle of rats after cryoinjury. METHODS: A total of 60 rats were divided randomly into six groups are: (1) Control (n = 5), (2) sham control (n = 5), (3) Group adaptation (n = 5) and two experimental groups sacrificed after 7, 14 and 21 days (4) cryoinjuryed and treated with aquatic exercise (n = 15), (5) cryoinjuryed and untreated (n = 15) and (6) without injury and submitted to aquatic exercise (n = 15). The aquatic exercise sessions were conducted 6 times a week and each session lasted for 90min. At the end of the protocol the animals were sacrificed and total mRNA was extracted for analysis of MyoD and myogenin and morphological analysis of the lesion. RESULTS: The results revealed an increase in MyoD mRNA 7 days swimming group when compared to other groups. With respect to the expression of myogenin was found a significant increase after 14 days in the swimming group compared to group the same period with the injury and 7 days groups. 14 days swimming group in the expression of myogenin showed similar to the control and sham groups, no statistically significant differences were found. Regarding the morphology showed that the muscles of the control group showed normal histological aspect. The sham group showed edema, myonecrosis and inflammatory infiltration in grade 1. In groups 7, 14 and 21 days, there were no statistically significant differences in four stages of tissue remodeling evaluated (inflammatory infiltration, edema, necrosis and immature muscle fibers) between the injured groups compared to groups with lesions and water treatment CONCLUSION: The aquatic exercise induced changes in the expression of myogenic markers during the repair process of skeletal muscle of rats after cryoinjury.